Career Counselor’s Self-Efficacy and Job Satisfaction across the Gender in Professionals and Internees - Bibi Hajra; Tamkeen Saleem; Syed Jawad Zareen (Indus Journal of Social Sciences, 2025)
Career counselor’s self-efficacy indicates counselor’s belief about his/her ability to demonstrate specific counseling skills (Lent, 2006) and job satisfaction is a pleasurable or positive emotional state from the appraisal of one’s job or experience. The present study was purposed to investigate career counselor’s self-efficacy and job satisfaction in mental health counselors and educational counselors at professional and internee’s level. A sample of 80 counselors was taken males n=24, females n=55out of which 24 were educational counselors and 55 were mental health counselors. Data was collected from psychology/Psychiatric departments of different hospitals and universities of Islamabad and Rawalpindi. The result indicates that there is no gender difference on self-efficacy and job satisfaction in career counselors and experience is related with job satisfaction and self-efficacy.